Bisphenol-A carbonate dimer is a more preferred substrate for laccase mediated degradation than the Biphenol-A in its monomeric and dimeric forms. (November 2018) - Divya, Lakshmanan M.; Prasanth, Ganesh K.; Arun, Kumar G.; Sadasivan, C.
Abstract: Bisphenol A (BPA), a known endocrine disrupting chemical is used as a primary monomer in most of the day to day consumables. Though enzyme laccase secreted by certain microbes are known to catalyze the removal of BPA, their mode of interaction remains unresolved. Here we propose a mechanism underlying the interaction between laccase and the three forms of BPA; BPA carbonate dimer and BPA monomer which easily leach out from polycarbonate plastic, and BPA dimer formed by laccase mediated BPA oxidation. The result indicated that there is a high degree of propensity for the carbonate dimeric form of BPA to interact with laccase when compared to BPA monomer and dimer (formed by laccase mediated BPA oxidation), owing to the tunnel like arrangement of the active site, which is large enough to accommodate dimeric or higher forms of BPA and due to the flexible confirmation of BPA carbonate dimer. Besides carbonate dimer is less stable than BPA dimer and has more number of H- bonds, with the key catalytic residues within the active site of the laccase, than monomers and dimers and hence has more chances of getting cleaved and degraded faster. Laccase catalyzed BPA dimers on other hand are less flexible and more stable and hence has more probability to form nontoxic polymers, which can be sieved out later after treatment process. Our proposed mechanisms on BPA-Laccase interaction provide explanation to the previous observations on the laccase catalyzed removal of BPA and formation of its oxidative products. Highlights: Mechanism underlying the interaction between BPA and enzyme Laccase is proposed. High degree of propensity for BPA dimer to interact with laccase than its monomer. The oxidized free radical of carbonate dimers undergo decomposition. The oxidized free radical of BPA dimers undergo successive polymerization.